Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1097/md.0000000000000594
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency Is an Independent Risk Factor for Urinary Tract Infections After Renal Transplants

Abstract: Vitamin D deficiency is frequently found in patients with renal transplants (RTxs). Because vitamin D plays indispensable roles in the immune system, there may be an association between vitamin D deficiency and infection in these patients, but this has not been fully elucidated. Therefore, this study investigated the impact of pre-RTx vitamin D deficiency on urinary tract infection (UTI) development after RTx.We measured 25-hydroxyvitamin D3 (25(OH)D3) levels in 410 patients 2 weeks before they underwent RTx. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
4
19
0
2
Order By: Relevance
“…Biological plausibility was supported by the dose‐response gradient observed between lower quartiles of serum 25(OH)D levels and infection susceptibility, with a 24% decrease in the risk of overall infection per each one‐quartile increase. Our results reinforce recent studies suggesting the clinical relevance of the immunomodulatory role attributable to vitamin D in the setting of ongoing immunosuppression after KT.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Biological plausibility was supported by the dose‐response gradient observed between lower quartiles of serum 25(OH)D levels and infection susceptibility, with a 24% decrease in the risk of overall infection per each one‐quartile increase. Our results reinforce recent studies suggesting the clinical relevance of the immunomodulatory role attributable to vitamin D in the setting of ongoing immunosuppression after KT.…”
Section: Discussionsupporting
confidence: 90%
“…In a single‐center retrospective study, Park et al found serum 25(OH)D levels <20 ng/mL at baseline were associated with a higher incidence of bacterial infection and, specifically, urinary tract infection (UTI). Similar findings were reported by Kwon et al, although restricted to late‐onset UTI episodes. Rech et al demonstrated in a small cohort of KT recipients a significant association between serum 25(OH)D levels <20 ng/mL (measured 30 days before or after transplantation) and the occurrence of opportunistic viral infection.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Notably, also in an additional analysis of opportunistic infections, we could not detect an association with vitamin D status (Table S1). These findings are in line with the results of Ban Th et al Few studies, most of them based on retrospective data collection, reported an association between vitamin D deficiency and infections . The cutoff value used for definition of vitamin D deficiency in our study is based on studies that considered dynamics in bone turnover variables .…”
Section: Discussionsupporting
confidence: 92%
“…In the general population, deficiency of vitamin D has been associated with a higher risk of infections . Among kidney transplant recipients, some studies indicate a relevance of 25‐OHD levels for infections overall, bacterial infections, urinary tract infections, and opportunistic viral infections . Other studies could not identify an association between vitamin D status and infections after kidney transplantation .…”
Section: Introductionmentioning
confidence: 99%